1993
DOI: 10.2136/sssaj1993.03615995005700050001x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Hydraulic Functions from Transient Outflow and Soil Water Pressure Data

Abstract: Inverse solution techniques currently used for estimating unsaturated soil hydraulic functions from laboratory outflow experiments use cumulative outflow only in combination with initial and final soil water pressure head values. Additional soil water information is needed to improve the estimation procedure and to minimize uniqueness problems. It was the objective of this study to experimentally explore the feasibility of using both cumulative outflow and soil water pressure head data in the inverse solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(104 citation statements)
references
References 0 publications
7
97
0
Order By: Relevance
“…Their results showed that multi-step tests can contain sufficient information for unique estimates while one-step tests show poorer estimations. On the other hand, Eching and Hopmans (1993) conducted both one-step and multi-step outflow experiments, and with the inclusion of pore water pressure data in the inverse methods, both onestep and multi-step methods gave excellent results with the optimized parameters agreeing well with the independently measured p-θ data. Since the multi-step tests took twice as long to perform as the one-step tests, it was concluded that the one-step test is still an attractive option if pore water pressure measurements are available.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Their results showed that multi-step tests can contain sufficient information for unique estimates while one-step tests show poorer estimations. On the other hand, Eching and Hopmans (1993) conducted both one-step and multi-step outflow experiments, and with the inclusion of pore water pressure data in the inverse methods, both onestep and multi-step methods gave excellent results with the optimized parameters agreeing well with the independently measured p-θ data. Since the multi-step tests took twice as long to perform as the one-step tests, it was concluded that the one-step test is still an attractive option if pore water pressure measurements are available.…”
mentioning
confidence: 85%
“…Multi-step tests, in which applied pneumatic pressure or suction is changed stepwise with small increments, have also been conducted (Eching and Hopmans, 1993;Eching et al, 1994;van Dam et al, 1994). van Dam et al (1994) carried out both one-step and multi-step experiments and compared the optimized parameters using only cumulative outflow as the input data.…”
mentioning
confidence: 99%
“…[15] A series of multistep out-and inflow experiments [e.g., Eching and Hopmans, 1993] was performed to estimate the hydraulic properties of the three sands. Plexiglas columns with an inner diameter of 5.4 cm and a filter plate at the bottom were carefully filled with sand to a height of about 34 cm using the same filling tube as for preparing the layers of the heterogeneous tank.…”
Section: Multistep Column Experiments To Estimate Hydraulic Parametermentioning
confidence: 99%
“…Inverse solutions based on the Richards equation are now increasingly used for estimating the unsaturated soil hydraulic properties. An advantage of this approach is that the retention and hydraulic conductivity functions can be estimated simultaneously from transient flow data, as shown by many past and recent studies (Abbasi et al, 2003;Abbaspour et al, 1999;Dane and Hruska, 1983;Eching and Hopmans, 1993;Kool and Parker, 1987;Lazarovitch et al, 2007;Minasny and Field, 2005;Ritter et al, 2003;Russo et al, 1991;Schwarzel et al, 2006;Sonnleitner et al, 2003;Zachmann et al, 1981). The soil hydraulic parameters are then obtained by minimizing an objective function, usually defined as the sum of squared deviations between observed and predicted transient water flow variables (Hopmans et al, 2002).…”
Section: Introductionmentioning
confidence: 99%